Penguatan Kompetensi Jaringan Fiber Optik bagi Siswa SMK SWASTA YAPIM BIRU BIRU dalam Rangka Persiapan Praktik Kerja Industri - Sinaga, Lotar Mateus; Sipayung, Sardo Pardingotan; Ginting, Anirma Kandinda; Harianja, Andy Paul (Fakultas Ilmu Komputer, Universitas Katolik Santo Thomas Medan, 2025)
Student readiness for Industrial Work Practice (Prakerin) is a crucial component of vocational education, particularly in the Computer and Network Engineering (TKJ) program. This study aims to enhance the technical competence of students at SMK Swasta YAPIM Biru-Biru in the field of fiber optic networking, a key technology widely adopted in the networking and telecommunications industries. The competency strengthening program was conducted through intensive training covering theoretical foundations of fiber optics, installation practices, splicing techniques, testing procedures, and basic maintenance. Evaluation methods included pre-tests, post-tests, and observation of students' practical skills. The results showed a significant improvement in both conceptual understanding and hands-on abilities following the training. This program is expected to equip students with the confidence and technical proficiency required to undertake their industrial work practice successfully. Furthermore, this initiative reflects a strong synergy between educational institutions and the industry in preparing skilled vocational graduates who are responsive to technological advancements.